1998
DOI: 10.1046/j.1365-2133.1998.02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic endemic hydroarsenicism

Abstract: Chronic endemic hydroarsenicism in a 48-year-old man from Antofagasta, Chile, is reported. The literature on the global health problems of hydroarsenicism is reviewed, especially with regard to the carcinogenic action of arsenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
6
1
Order By: Relevance
“…Our data also showed such an association. Although it is widely accepted as a risk factor, 32,33 we did not find in our study that subjects who underwent arsenic therapy were at high risk for sporadic BCC. This might be because only four cases and one control had a positive history of arsenic therapy.…”
Section: Discussioncontrasting
confidence: 87%
“…Our data also showed such an association. Although it is widely accepted as a risk factor, 32,33 we did not find in our study that subjects who underwent arsenic therapy were at high risk for sporadic BCC. This might be because only four cases and one control had a positive history of arsenic therapy.…”
Section: Discussioncontrasting
confidence: 87%
“…32 The clinical manifestations of arsenicosis in the skin showed a high prevalence (9AE1 cases per 100 inhabitants). [33][34][35][36][37] This Table 2 Characteristics of the adult and paediatric populations, exposed and not exposed to mine tailings 37 Also, our results are similar to those reported by Guha et al, 13 Kadono et al 8 and other authors who found that the most frequent cutaneous manifestation of chronic endemic hydroarsenicosis was keratosis, affecting more males [33][34][35][36][37] than females. Although the toxicity produced by mine tailings is commonly acquired through drinking water, our study found that the most common routes for arsenic poisoning are inhalatory and percutaneous.…”
Section: Discussionsupporting
confidence: 90%
“…The clinical manifestations of arsenicosis in the skin showed a high prevalence (9·1 cases per 100 inhabitants) 33–37 . This value is similar to that reported by Guha et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…also reported that sodium dimercaptosulfonate, a less toxic BAL salt, given as two courses of 0.25 mg oral daily for 3 days each can improve pruritus and arsenic‐induced keratoses 34 . Other case reports noted the use of 5%–10% salicylic acids in reducing hyperkeratosis suspected to be caused by chronic arsenic exposure 27,48,49 . Five case reports suggested that in presentations where there may be hyperkeratosis with concurrent cutaneous malignancies, individuals may respond well with oral retinoids such as acitretin, dose ranged 10–25 mg/day, in combination with other management strategies 23,27,47,50,51 …”
Section: Resultsmentioning
confidence: 99%